Meningkatkan Kemampuan Sosial Anak Usia Dini Melalui Pembiasaan Salam, Senyum, dan Sapa Di TK IT Insan Madani - Arneta Widia; Nurlaili Nurlaili (Universitas Islam Negeri Sumatera Utara, 2026)
Early childhood social skills need improvement, particularly in children's confidence to interact, greet others, and demonstrate positive social behavior in the school environment. This study aimed to improve the social skills of children aged 5–6 years through the habituation of greetings, smiles, and salutations (3S) at TK IT Insan Madani. The study employed Classroom Action Research using the Kemmis and McTaggart model conducted in two cycles. The participants were 15 children in Group B aged 5–6 years, while the object of the study was children's social skills. Data were collected through observation and documentation and analyzed using quantitative and qualitative descriptive techniques. The findings showed an improvement in children's social skills from 48.3% in the pre-cycle stage to 66.7% in Cycle I and 81.7% in Cycle II. The 3S habituation was proven effective in enhancing children's social skills. Teachers are recommended to implement the 3S habituation consistently to support children's social development.